The Effectiveness of Implementing a Project-Based Learning Model in Enhancing Student Collaboration in the Development of Game-Based Media - Firdiawan Ekaputra (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to examine the effectiveness of project-based learning model in improving student collaboration in game-based media development. This research is a pre-experimental research because the research sample consists of one experimental class and does not involve a control class. In this study, the sample used was 21 students from the Jambi University Chemistry Education Study Program who took the chemistry learning gamification course in the 2023/2024 academic year. The method used to collect student collaboration data is the questionnaire method. Data on collaboration in the sample class were collected twice, namely before and after the application of the project-based learning model in the sample class. The hypothesis test results obtained a significance value of 0.00 or smaller than 0.05, so that the application of the project-based learning model was effective in improving student collaboration skills in the sample class. In this study, it can be concluded that applying a project-based learning model improves students' ability to work together.